Kinematics of running at different slopes and speeds - Padulo, J.; Annino, G.; Migliaccio, G. M.; D'Ottavio, S.; Tihanyi, J. (The Journal of Strength and Conditioning Research, 2012)
The aim of this study was to verify the influence of the combination of different running speeds and slopes based on main kinematic parameters in both groups of elite (RE) and amateur (RA) marathon runners. All subjects performed various tests on a treadmill at 0, 2, and 7% slopes at different speeds: 3.89, 4.17, 4.44, 4.72, and 5.00 m·s. A high speed digital camera, 210 Hz, has been used to record; Dartfish 5.5Pro has been used to perform a 2D video analysis. Step length (SL), step frequency (SF), flight time (FT), and contact time (CT) were determined and used for comparison. SL, SF, and FT parameters increased, and CT parameter decreased as speed increased. As slopes increased, SL and FT decreased and SF increased in both groups and only CT decreased in RE, whereas in RA, it increased. Data were fitted to the linear regression line (R > 0.95). The 2 groups were significantly different (p < 0.05) in FT, SL, and SF at all speeds in level running. A significant difference between the 2 groups was found in FT at 2 and 7% slopes at all speeds (p < 0.05). Percentage alterations in all variables were greater in the RA group. In conclusion, the choice of optimum SL and SF, through efficient running can be maintained, is influenced not only by speed but also by slopes. Elite runners perform more efficiently than amateur runners who have less experience.